Cajanegrización (2024)
In Cajanerizacion I addressed the relationship between the notion of "living" and its interaction with the environment, as I have experienced it at some point in my life and I see it reflected daily in the nomadic street dwellers (cyberlokos). The idea I propose is the duality between nomadic life and the construction of temporary habitats. This duality explores two ways of interacting with the environment: nomadic life, characterized by mobility and adaptation to different places, and the creation of habitable spaces. temporary ones that provide a sense of roots and belonging. While nomadic life involves constant adaptation, temporary habitats offer a temporary home. This contrast makes us reflect on the relationship between mobility and stability, as well as the meaning of "inhabiting" a place and how it influences our perception of space, time and our connection with nature and the community.